Rock Art and Archaeology – a Short Visit to Zolat el Hammad, Northern Sudan - Jesse, Friederike (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2020)
The striking sandstone formation of Zolat el Hammad is located in the southern Libyan Desert, about halfway between the Middle Wadi Howar and El Atrun. The place has been known for its numerous rock engravings for more than a hundred years. Wild and domesticated animals as well as few human figures are depicted. Cattle engravings largely dominate, followed by giraffes and ostriches. In 1997 the first paintings were discovered in a small rock shelter. Very schematic bovids are drawn in red and white colour. However, even though it is one of the most remarkable rock art sites in this part of the Sahara, Zolat el Hammad has never been intensely studied. Observations on rock art and archaeology made during a short stay in 2001 are the basis for presenting an account of the area with the aim of encouraging further research on it
ill. ; 24 cm
Keywords: Northern Sudan; Libyan Desert; Zolat el Hammad; rock art; archaeology